Building a Community of Learners In and Outside the Classroom - Laverick, Erin Knoche (Journal of International Students, 2018)
Learning Communities (LCs) and First-Year Seminars (FYS) are common support systems for college students. This article explores the use of such systems with undergraduate international students in their first semester of study as a means to help them better acclimate to campus life and rigorous classroom expectations.